Engaging in Dialogue on U.S. Foreign Policy - Fares Center for Eastern Mediterranean Studies (Tufts Archival Research Center, 2005)
Occasional Paper No. 1; A report on the conference Engaging in Dialogue on U.S. Foreign Policy, November 8-9, 2004, Tufts University, Medford/Somerville, MA.